SEKURITISASI ASET SEBAGAI PELUANG BISNIS DAN PENINGKATAN SOLVABILITAS PERUSAHAAN - Vera Intanie Dewi (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
Securitization is a recent innovation in asset sales. It involves the pooling and repackaging of loans into securities that are then sold to investors. Securitization was originated in 1970, when the Government National Mortgage Association (GNMA) developed the GNMA pass-through, a mortgage-backed security. Since then commercial banks, savings and loan associations, and various non-deposit-based firms have securitized multifamily and commercial mortgage loans, automobile loans, credit card receivable, various trade receivables, and other types of assets. The benefits from securitization include protection from interest-rate risk, increased liquidity and diversification for original lenders and for investors; a more efficient flow of capital from investors to borrowers. Securitization may enable institutions to attract long-term funds which are more profitable than institutions using conventional tools, and it also provides the originator with a new source of fee income from originating and servicing the securitized assets.